Orthodoxy revisited: the postsecular classroom - Sutton, Timothy J. (Journal of beliefs and values, 2018)
As is the case with many new intellectual concepts, the definitional parameters of the term "postsecular" are in flux and ultimately will shape its critical usefulness. This article represents an effort to participate in this discussion with a particular emphasis on the pedagogical importance of the tenets of religious orthodoxy when discussing spiritual matters in the university-level liberal arts classroom. The analysis is contextualized by reflection on the place of religion in the public sphere by various scholars, including Jürgen Habermas and Rowan Williams. This analysis establishes that the study of traditional religious positions in the university classroom can enrich the discourse of the liberal arts; however, neither proselytization nor an emotion-based spiritual paradigm bereft of intellectual rigor will serve these ends. I argue that the re-introduction of religion into analytical discourse in the humanities classroom will be successful if the discussion of religion is complemented by the recognition of the serious study of religious thought and scholarship. The argument is then developed through a pedagogical case study of Evelyn Waugh's Brideshead Revisited that illustrates how the discussion of orthodox positions can enhance discussion of the novel in the postsecular classroom.